PERBANDINGAN ANTARA ROLE MODEL KEPEMIMPINAN SEKOLAH DAN MADRASAH DALAM PERSPEKTIF PENDIDIKAN - Agustina, Pina; Malah, Sofiyatur; Aisyah, Azlina; Fernando, M.Rizky; Mardiyah, Mardiyah (STKIP Pesisir Selatan, 2026)
This study aims to analyze the comparison of leadership role models between school principals and madrasa principals from an educational perspective and to provide a more comprehensive understanding of the differences in their leadership characteristics. The approach used in this study is a qualitative approach with a comparative descriptive design through a literature study by utilizing various sources such as scientific journals, academic books, and relevant previous research. The data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The results show that school principal leadership tends to focus on innovation, professional management, and adaptation to digital technology development, while madrasa principal leadership emphasizes the integration of educational innovation with the internalization of religious values. These differences are influenced by institutional characteristics, regulations, and educational goals of each institution. The novelty of this study lies in the comparative analysis that examines both leadership models within an integrated framework, thereby providing new insights into the differences and uniqueness of leadership in schools and madrasas.